Pengaruh Digital Marketing terhadap Keputusan Pembelian Brand Nibras dengan Kepercayaan Konsumen sebagai Variabel Moderasi - Nurrohmah, Shinta; Listian Indriyani Achmad; Sakum; Sukron Mamun (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to test and explain the effect of digital markerting variables on purchasing decisions for the Nibras brand. In addition, it is also to test and explain the consumer confidence variable in moderating digital marketing variables on purchasing decisions for the Nibras brand. This type of research uses quantitative research, the aim is to get answers about the clarity of the relationship between variables through data analysis to test the hypothesis that has been set. This study uses a probability sampling technique of simple random sampling type, which is a type of research that is carried out randomly on each element without regard to strata in the population. There are 100 samples that are feasible in the study. Based on the characteristics of research respondents from a gender perspective, 71% of female respondents and 29% of male respondents. The results of the SEM PLS analysis state that digital marketing variables have a significant positive effect on purchasing decisions. That way H1 is accepted and H2 is accepted. As for the moderating role of the consumer confidence variable for digital marketing variables on purchasing decisions. The consumer confidence variable moderates the effect of digital marketing on purchasing decisions, and the type of moderation is quasi moderation. With that stated that H1 is accepted and H2 is accepted.